Ecological risk evaluation of spent engine oil pollution using earthworm and microbial bioassays - Azorji John Paul Nnawuike; Angela Chika Udebuani; Nwachukwu Udodi Chibuike; Igwe Charles Ekene; Dike Kelechi Stanley; Nzenwa Peter Odinaka; Igbokwe Moses Chukwuebuka (Sustinere: Journal of Environment and Sustainability, 2024)
The study aimed to assess the ecotoxicological risk associated with the indiscriminate disposal of spent engine oil on terrestrial ecosystem using earthworm and microbial assays. Soil samples were collected from a depth of 0-20 cm and subjected to standard analytical protocols for analysis. Earthworms (assessed by mortality rate) and microorganisms (evaluated for inhibitory effects) covered a wide range of short-term lethal and sub-lethal endpoints used for risk characterization, analyzed through Probit analysis. The result of acute toxicity assay revealed that microbial absorbance rated depended on the dose and type of organism, ranking in the order: Acinetobacter > Enterobacter > Bacillus species >Pseudomonas. Aas oil concentratoin increase, mortality among earthworm was observed.  Risk Quotient (RQ) values for Zea mays, Vigna unguiculata, Glycine max and earthworm varied from low to very high risk based on estimated Predicted No Effect Concentration (PNEC) values. Microorganisms exhibited differing level of biotolerance to spent engine oil exposure as indicated by respective risk quotient values. Exposure to spent engine oil posed minimal risk to Pseudomonas sp., Bacillus sp., and Acinetobacter sp.,  with RQ values below unity (< 1). Conversely, Enterobacter sp. Showed a high risk with values above unity. Earthworms play a pivotal role in agriculture due to their numerous economic benefots. Soil microorganisms are essential for maintening soil quality by performing vital processes. The antimicrobial properties of spent engine oil on soil may distort microbial activities, potentially inhibiting their growth and leading to alterations in ecological functionality of the soil.